Improving Student Mathematics Learning Outcomes with The Learning Model Cycle 5e Class VII - Halidin Saima; Made Subawo; Arbain Arbain (USN Kolaka, 2023)
This research is a Classroom Action Research that aims to find out whether The Learning Cycle 5e Model can improve mathematics learning outcomes. The subjects of this study were students of class VIIc MTS Al-Ikhlas Iwoimenda, as many as 34 students—retrieval of data with test results and observation sheets. Observation sheet data and mathematics learning achievement tests were analyzed using descriptive statistics. The results achieved after implementing the action through The Learning Cycle 5e Model for two cycles: a) the average score of learning outcomes in the first cycle was 63.10 froman ideal score of 100 and is in the excellent category. It increased in the second cycle to 78.43 from an ideal score of 100 and was in the excellent category. b) There was an increase in the percentage of observations of student activity in the first cycle of the first meeting by 41.67%, the second meeting was 66.67%, and the second cycle first meeting was 83.33%, the second meeting was 91.67%. From the research results on these data, the Learning Cycle 5e Model on operational material and properties of integer operations can improve the mathematics learning outcomes of class VIIc MTS Al-Ikhlas Iwoimenda.